Volumetric Analysis of 3-D Resistivity Distribution of Leachate Plume in Third Cemetery, Benin, South-South, Nigeria - Idehen, Osabuohien (JOURNAL OF ADVANCES IN PHYSICS, 2020)
This paper aims to carry out the volumetric analysis of 3-D resistivity distribution of leachate plume in Third Cemetery, Benin City, South-South, Nigeria. If not appropriately located or not sufficiently protected, cemeteries pose a significant health problem for the people (Fisher and Croupkamp,1993). Health concern about the possible impact of the cemeteries in Nigeria on the water supply has prompted this research. The research engaged 2-Dimensional and 3-Dimensional imaging (tomography) to investigate the presence and migration of leachate plumes in the cemetery and computation of time-lapse to detect the time rate of migration in both the vertical and horizontal directions. The geoelectric models obtained for the surveys displayed leachate plumes starting from the laterite (the burial environment) down to the sandy formation (the regional water supply source). The leachate plumes presence in the sand bed is modeled and described as shown in the 2-D and 3-D displays. This study showed that parts of the cemetery had been contaminated. This contamination was also observed to have infiltrated into the aquifer in the cemetery. 3-D block model, using Voxler 4.0 software was employed to carry out the volumetric analysis of the 3-D resistivity distribution of leachate plume in the Third Cemetery.